Examining the Effectiveness of Quizizz on the English Proficiency of Ninth-Grade Students in a Selected Boarding Middle School - Jiaming Dong; Carmela S. Dizon (International Journal of Education and Humanities, 2026)
This study examined the effectiveness of a Quizizz-based homework intervention in improving junior high school students’ English achievement. Two intact Grade 9 classes in a public junior high school in China participated in the study, with one class (n = 46) assigned as the experimental group and the other (n = 43) as the control group. Both groups completed a researcher-developed pre-test and post-test assessing vocabulary, grammar, reading comprehension, and overall English performance. The experimental group received four weeks of Quizizz-based homework aligned with the lessons, while the control group completed equivalent paper-based assignments. Statistical analyses included descriptive statistics, reliability testing, normality testing, paired-samples t-tests, and independent-samples t-tests. The results showed that the two groups had comparable baseline proficiency across all components. The experimental group demonstrated significant improvements from pre-test to post-test in vocabulary, grammar, reading, and total English scores, whereas the control group showed minimal or negative changes. Post-test comparisons further revealed that the experimental group outperformed the control group across all components. Gain-score analysis confirmed substantially greater improvements in the experimental group. Overall, the findings indicate that Quizizz-based homework is an effective and engaging approach for enhancing English achievement among junior high school learners